Anterior chest wall reconstruction for cutaneous involvement of Hodgkin’s lymphoma - Ishak, Ariffuddin; Mat Saad, Arman Zaharil; Wan Sulaiman, Wan Azman; Husin, Azlan; Halim, Ahmad Sukari (Journal of Surgery and Medicine, 2019)
Hodgkin lymphoma with initial thoracic involvement is common and it is more frequently localized in the mediastinum, followed by lung parenchyma and the pleura. However, skin involvement of Hodgkin’s lymphoma is extremely rare. We report this case to illustrate a rare and unique presentation of a potentially curable disease, with resistance to standard treatment. Free tissue transfer was used as an adjunct to provide a better quality of life for the patient with Hodgkin lymphoma complicated with extensive anterior chest wall ulceration exposing lung and pericardium.